YI.4 Gonococcal Genomics Shows Impact of Recombination on Obscuring Phylogenetic Signal and Disseminating Resistance Loci. (13th July 2013) - Grad, Y; Kirkcaldy, R; Dordel, J; Goldstein, E; Trees, D; Weinstock, H; Parkhill, J; Hanage, W P; Bentley, S; Lipsitch, M
Abstract : Background: Recombination plays a significant role in the plasticity of the Neisseria gonorrhoeae genome by generating antigenic diversity and as a mechanism of spread of antibiotic resistance elements. Extensive recombination in a population can also limit inferences about phylogenetic history. Here, we investigate the impact of recombination in the study of isolates with reduced susceptibility to cefixime (cef RS ; cefixime MICs ≥ 0.25 µg/ml) in the United States. Methods: We generated draught genome sequences for 242 gonococcal isolates collected by CDC's Gonococcal Isolate Surveillance Program (GISP). These isolates comprise all 141 cef RS isolates from GISP in 2009–10 and 141 susceptible isolates matched by location, collection date, and sexual orientation of the infected individual. We predicted recombinant regions and generated a maximum likelihood phylogenetic tree from core SNPs. We performed in silico MLST and NG-MAST typing, and compared phylogenies of antibiotic resistance loci to whole genome-based phylogenies. Results: Per site r/m ratios (relative likelihood that a polymorphism was introduced through recombination rather than mutation) of recent branches in the phylogenetic tree are higher and fraction of homoplasic sites much lower than for the overall tree, suggesting that extensive recombination reduces confidence in the phylogeny's deep branches. Comparison with in silico MLST and NG-MAST reveals that traditional typing-based phylogenetic inferences, even for recent events, are confounded by recombination. Of the 21 penA alleles in this dataset, mosaic PBP2 pattern XXXIV was the most common (present in 116/121 cef RS isolates). We find several recombination events introducing this allele into distinct lineages, and an event within the dcw gene cluster, which includes the penA allele, associated with reversion from cef RS to cefixime susceptibility. Conclusions: Genomic methods reveal the impact of recombination on phylogenetic history, spread of resistance elements, and genome evolution, and offer a superior approach to traditional typing schemes in understanding population structure and dynamics.